Mode of organization of lipid aggregates: A conformational analysis. Issue 3 (March 1984) - Brasseur, Robert; de Kruijff, Ben; Ruysschaert, Jean-Marie
Abstract : A computational approach is used to predict the mode of organization of lipid molecules. The calculated aggregate states are fully compatible with the lipid phase preference: bilayers for dipalmitoylphosphatidylcholine, micelles for palmitoyllysophosphatidylcholine, and inverted structures for protonated dioleoylphosphatidic acid. The minimal conformational energy of the isolated molecule is calculated as the sum of the contributions resulting from the Van der Waals interactions, the torsional potentials, the electrostatic interactions, and the transfer energy. Assembly of these structures in monolayers yields the most probable modes of organization of lipids. The described method may represent a useful toot to predict the phase preference of lipids and to give a molecular description of their mode of association.